Difference between revisions of "Math 22 Asymptotes"
Jump to navigation
Jump to search
Line 2: | Line 2: | ||
If <math>f(x)</math> approaches infinity (or negative infinity) as <math>x</math> approaches <math>c</math> from the right or from the left, then the line | If <math>f(x)</math> approaches infinity (or negative infinity) as <math>x</math> approaches <math>c</math> from the right or from the left, then the line | ||
− | '''Example''': Find the | + | '''Example''': Find the a vertical Asymptotes as below: |
− | '''1)''' <math>\ | + | '''1)''' <math>f(x)=\frac{x+3}{x^2-4}</math> |
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Solution: | !Solution: | ||
|- | |- | ||
− | | | + | |Notice <math>f(x)\frac{x+3}{x^2-4}=\frac{x+3}{(x-2)(x+2)}</math> |
|- | |- | ||
− | | | + | |Let the denominator equals to zero, ie: <math>(x-2)(x+2)=0</math>, hence <math>x=-2</math> or <math>x=2</math> |
|- | |- | ||
− | |Therefore, <math> | + | |Therefore, <math>f(x)</math> has vertical asymptotes at <math>x=2</math> and <math>x=-2</math> |
|} | |} | ||
− | '''2)''' <math>\ | + | '''2)''' <math>f(x)=\frac{x^2-x-6}{x^2-9}</math> |
{| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | {| class = "mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Solution: | !Solution: | ||
|- | |- | ||
− | |Notice <math>x\ | + | |Notice <math>f(x)\frac{x^2-x-6}{x^2-9}=\frac{(x-3)(x+2)}{(x-3)(x+3)}=\frac{x+2}{x+3}</math> |
|- | |- | ||
− | | | + | |Let the denominator equals to zero, ie: <math>(x+3)=0</math>, hence <math>x=-3</math> |
+ | |- | ||
+ | |Therefore, <math>f(x)</math> has vertical asymptote at <math>x=-2</math> | ||
|} | |} | ||
+ | |||
This page is under construction | This page is under construction | ||
Revision as of 07:07, 4 August 2020
Vertical Asymptotes and Infinite Limits
If approaches infinity (or negative infinity) as approaches from the right or from the left, then the line
Example: Find the a vertical Asymptotes as below:
1)
Solution: |
---|
Notice |
Let the denominator equals to zero, ie: , hence or |
Therefore, has vertical asymptotes at and |
2)
Solution: |
---|
Notice |
Let the denominator equals to zero, ie: , hence |
Therefore, has vertical asymptote at |
This page is under construction
This page were made by Tri Phan